Electrocardiogram 12 Lead in Transverse Plane Based on Computer - Octantri, YB. Rischa Via; Ariswati, Her Gumiwang; Syaifudin, Syaifudin (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2019)
An electrocardiogram (ECG) is a graph produced by an electrocardiograph to detect heart abnormalities by measuring the electrical activity produced by the heart. Heart disease currently represents 16% of total deaths from all causes. Based on data from the Basic Health Research (Riskesdas) in 2018, the incidence of heart disease is increasing from year to year. At least 15 out of 1000 people, or about 2,784,064 individuals in Indonesia suffer from heart disease. The purpose of this research is to make a 12 lead electrocardiogram (ECG) PC based with storage (transverse plane) to make it easier for users to see the condition of heart signals. The contribution of this research is that devices can display heart signals on a computer and the results can be saved in the form of images and excel. This study used a pre-experimental method. The ECG signal is obtained from the phantom which is connected using an ECG cable. The results of the leads are in the form of heart signals and BPM which will be processed on the microcontroller and then the results will be displayed on a computer and can be saved. Measurement of the BPM value using Phantom on V2 obtained an error value of 0.25% for 120 BPM, 0.125% for 240 BPM. The maximum limit in the BPM error tolerance is ±5%. The results showed that the system as a whole worked well. The shape of the V2 signal generated by the module is the same as the manufacturer's ECG.